Use of graphite in the distribution of rice seeds with constant flow seed metering device - Savi,Daniel (2023)
ABSTRACT The performance of the seed metering mechanism is evaluated according to the deposition uniformity during its operation and interference in the seed quality. The study aimed to assess the influence of graphite on the deposition homogeneity and the break index of rice seeds, distributed with a constant flow metering device with different exposition rates of the fluted roller. The rice seeds were treated with 4 g of graphite per kilogram and had a sowing density of 100 kg ha-1. The completely randomized design was arranged in a double factorial scheme (2 × 5). The first factor was the use of graphite, and the second was the fluted roller exposition rate (20; 40; 60; 80; and 100%). The sowing density and the coefficient of variation were collected by gravimetry using a load cell. The use of graphite as a solid lubricant decreased the mechanical damage. Nevertheless, it also reduced the homogeneity in seed distribution. The increase of the roller exposition rate negatively interfered with the coefficient of distribution variation and positively with the break index of rice seeds, not influencing the sowing density. In this way, the use of graphite as a solid lubricant for sowing small grains distributed from the fluted rotor becomes promising.